In Times of Trouble: Innovative Drivers of External Competitiveness for Small Businesses during the Great Recession - Emanuele Brancati; Raffaele Brancati; Dario Guarascio; Antonello Zanfei (Global Labor Organization (GLO), 2020)
This paper analyzes the main drivers of external competitiveness in times of crisis for small and medium enterprises (SMEs). We focus on the Italian experience in the midst of the financial and sovereign-debt crisis, and present robust evidence based on a comprehensive survey of Italian companies in the manufacturing and production service sectors (the MET dataset). Overall, our results confirm the high degree of heterogeneity of the Italian system and the differences between internationalized and domestic companies in terms of performance as well as structural and behavioral dimensions. In particular, data highlight not only the strict correlation between internationalization and innovative activities but also a positive change of attitude of Italian firms towards these strategies. Our analysis shows that, whilst structural factors play a key role for external competitiveness, other critical firm-level aspects trigger superior performances, especially strategic profiles, technological capabilities, and proactive behaviors such as innovativeness and R&D investment. Importantly, we document disproportionate effects of innovation for smaller and less productive companies. This points at dynamic strategies as a potential tool to fill the gap between larger/more productive companies and the set of less structured firms, a segment representing an ideal target for policy measures.
Keywords: M20; L23; L25; 330; SME; external competitiveness; Great Recession